Synthesis and Biological Evaluation of Mannich Bases of Isoxazoline Derivatives as Novel Anti-Microbial Agents - Pawar Sudhir; Chavan Rajashree; Bhosale Ashok (E-Journal of Chemistry)
A novel series of compounds were synthesized by condensation reaction of substituted acetophenone (1a-b) with substituted aldehyde (2a-b) in presence of alcoholic sodium hydroxide to get intermediate chalcones (3a-c), which were further treated with hydroxylamine hydrochloride in presence of sodium hydroxide to get isoxazolines derivatives (4a-c). The latter were refluxed with substituted primary amines and formaldehyde for 6-10 h to afford Mannich bases. The synthesized compounds were characterized on the basis of their spectral (IR, 1HNMR) data and evaluated for the antimicrobial activity by using Zone of Inhibition by cup plate method and Minimum Inhibitory Concentration by broth dilution method.